Analisis Tingkat Kebisingan dari Aktivitas Landing Pesawat di Kawasan Bandara Djalaluddin Gorontalo - Tolinggi, Safrudin; Dengo, Moh. Rivandi (Jurnal Ilmiah Global Education, 2024)
Noise is defined as unwanted sound that can cause discomfort to the listener. Airports are one of the public facilities that have a vital role as a gateway for mobility in a city. The large number of planes landing and taking off causes high noise levels around the airport. Noise is the flow of energy in the form of waves, unwanted sounds with pressure that can vary based on the origin of the noise, so that it reaches the ears and improves hearing. Noise can disturb workers in the workplace due to psychological disorders and focus problems, which can cause a decrease in worker productivity. Workers with a working duration of 8 hours/day have a safe threshold value of 85 dB. That way, workers can work well, without experiencing disruption while working due to excessive noise levels. This research aims to determine the analysis of noise levels on Garuda Indonesia and Lion Air aircraft in the Djalaludin Gorontalo Airport working area in 2023. The research method used is quantitative descriptive. This activity will be carried out for 1 day, namely on Tuesday, October 3 2023 at Djalaludi Airport, Gorontalo. The data collected is primary data obtained directly from the results of measuring the noise level generated by Garuda Indonesia and Lion Air aircraft at Djalaludin Gorontalo Airport. From the results of measuring the noise level generated by Garuda Indonesia aircraft when landing, the result was 76.32. dB(A) and the results of measuring the noise level produced by the Lion Air plane when landing was 77.3 dB(A), where this measurement was carried out on the airport apron. Based on the threshold value of PERMENKES Number 2 of 2023, namely 75-85 dB(A) and based on the Decree of the Minister of Transportation of the Republic of Indonesia Number 52 of 2023 concerning the Master Plan for Djalaludin Airport, Gorontalo Regency, Gorontalo Province, namely 70-80 dB(A). The noise level produced by Garuda Indonesia and Lion Air planes is considered to be still normal